2011
DOI: 10.5152/eajm.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Glioblastoma Multiforme: A Case Report

Abstract: Malignant glioma development after trauma is a rare occurrence. We report a glioblastoma multiforme case that developed after a depressed skull fracture. A 65-year-old man was admitted because of right sided hemiplegia, epilepsy and changes in consciousness due to a malignant glial tumor. He had been operated on for a left calvarial depression fracture caused by cerebral laceration thirty-five years before. Radiologic imaging revealed a large contrast-enhanced mass lesion at the left frontotemporoparietal junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Our results have shown that in Southern Ontario between 2010-2013, there was a positive association between brain cancer risk and two health-related factors, namely traumatic injuries to the head and high body fat levels. Regarding THI, our findings were in accordance with previous studies from the medical sciences where severe head injuries were found to be a potential predisposing factor for the onset of brain cancer [58][59][60]. From a neurological perspective, Spallone et al [7] explained that cancerous brain tumors are commonly formed in the anatomical vicinity of sites where previous head injuries have occurred.…”
Section: Discussionsupporting
confidence: 91%
“…Our results have shown that in Southern Ontario between 2010-2013, there was a positive association between brain cancer risk and two health-related factors, namely traumatic injuries to the head and high body fat levels. Regarding THI, our findings were in accordance with previous studies from the medical sciences where severe head injuries were found to be a potential predisposing factor for the onset of brain cancer [58][59][60]. From a neurological perspective, Spallone et al [7] explained that cancerous brain tumors are commonly formed in the anatomical vicinity of sites where previous head injuries have occurred.…”
Section: Discussionsupporting
confidence: 91%
“…A strong association was recorded in the current study, finding that was in agreement with those from previous reports, in which a clear evidence for such a causative role was presented [73,[75][76][77]. Other authors suggested that GBM following a traumatic cerebral contusion is possible [24,78]. In some of those cases, the histopathological diagnosis was a prolongation of the gliotic scar of the tumor and persisting splinters were found in the glioma nests many years after TBI [72,75].…”
Section: Recent Genome Wide Association Studies (Gwas) Have Indicatesupporting
confidence: 93%
“…221 The paper was cited as a reference in the scientific literature as recently as 2011. 222 It would later be established by historians that Werner was one of at least 340 children and adolescents from the Brandenburg-Görden State Hospital who were murdered at the Brandenburg killing centre, so that their brains could be harvested for research at the KWI laboratories. ____ Julius Hallervorden was born in 1882 in Allenberg, East Prussia.…”
Section: Chapter 5 'There Was Wonderful Materials Among Those Brains'mentioning
confidence: 99%